The impact of cytomegalovirus reactivation and its treatment on the course of inflammatory bowel disease. Issue 7 (9th February 2014) - Delvincourt, M.; Lopez, A.; Pillet, S.; Bourrier, A.; Seksik, P.; Cosnes, J.; Carrat, F.; Gozlan, J.; Beaugerie, L.; Roblin, X.; Peyrin‐Biroulet, L.; Sokol, H.
Summary Background Consequences of latent cytomegalovirus (CMV) infection reactivation on inflammatory bowel disease (IBD) flare, as a flare‐worsening factor or simple bystander, are debated. Impact of anti‐viral treatment on IBD course is poorly known. Aim To assess the impact of CMV reactivation on patients hospitalised for IBD flare and the effect of anti‐viral treatment on IBD flare in patients with CMV reactivation. Methods First, a population of UC patients from Saint‐Antoine hospital, in flare with positive blood CMV PCR without anti‐viral treatment (n = 26), were compared to matched patients with negative blood CMV PCR in a case–control study. Secondly, a total of 110 hospitalisations between October 2003 and May 2012 for IBD flare‐up with CMV reactivation (80 diagnosed on blood PCR, 33 on tissue PCR) were identified in three French referral centres. Evolution following CMV reactivation diagnosis was compared between patients receiving anti‐viral treatment and those who did not. Results In the case–control study, no differences were observed between the two groups regarding length of hospital stay and colectomy rate. Comparing treated and untreated patients, no differences were observed at inclusion regarding age, gender, IBD type, immunosuppressant, CRP and haemoglobin level. No differences were observed regarding CRP level decrease at 10 days and colectomy rate at 3 months. Anti‐viral treatment was associated with lower serum albumin level at inclusion and longer hospitalisation. Conclusions CMV reactivation does not appear to alter the course of IBD flare. CMV treatment does not seem to impact the course of IBD. These results should be confirmed prospectively.